TGF-β1 Suppresses Proliferation and Induces Differentiation in Human iPSC Neural in vitro Models - Izsak, Julia; Vizlin-Hodzic, Dzeneta; Iljin, Margarita; Strandberg, Joakim; Jadasz, Janusz; Olsson Bontell, Thomas; Theiss, Stephan; Hanse, Eric; Ågren, Hans; Funa, Keiko; Illes, Sebastian (Frontiers in Cell and Developmental Biology, 2020)
Persistent neural stem cell (NSC) proliferation is, among others, a hallmark of immaturity in human induced pluripotent stem cell (hiPSC)-based neural models. TGF-β1 is known to regulate NSCs in vivo during embryonic development in rodents. Here we examined the role of TGF-β1 as a potential candidate to promote in vitro differentiation of hiPSCs-derived NSCs and maturation of neuronal progenies. We present that TGF-β1 is specifically present in early phases of human foetal brain development. We applied confocal imaging and electrophysiological assessment in hiPSC-NSC and 3D neural in vitro models and demonstrate that TGF-β1 is a signalling protein, which specifically suppresses proliferation, enhances neuronal and glial differentiation, without effecting neuronal maturation. Moreover, we demonstrate that TGF- β1 is equally efficient in enhancing neuronal differentiation of human NSCs as an artificial synthetic small molecule. The presented approach provides a proof-of-concept to replace artificial small molecules with more physiological signalling factors, which paves the way to improve the physiological relevance of human neural developmental in vitro models.